2001
DOI: 10.1159/000052809
|View full text |Cite
|
Sign up to set email alerts
|

Association of Comorbidity with Depressive Symptoms in Community-Dwelling Older Persons

Abstract: Background: Depression in later life poses a serious threat to mental health and well-being of older persons burdened with medical illnesses. Comorbid medical conditions independently, as well as through interactions, may influence the degree of depressive symptoms manifested by the elderly. Insight into the role medical comorbidity plays in the manifestation of depression may help to better address both physical and mental health care needs of the depressed elderly. Objective: To examine independent and syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
36
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 15 publications
9
36
1
Order By: Relevance
“…The prevalence of depression differed widely across specific medical illnesses. This finding is broadly consistent with those reported by other investigators Black et al, 1998;Lee et al, 2001;Mills, 2001;Dunlop et al, 2004;Chiu et al, 2005). The present study showed that subjective health and functional status explained all or most of the depression-chronic disease link for all chronic illnesses.…”
Section: Discussionsupporting
confidence: 94%
“…The prevalence of depression differed widely across specific medical illnesses. This finding is broadly consistent with those reported by other investigators Black et al, 1998;Lee et al, 2001;Mills, 2001;Dunlop et al, 2004;Chiu et al, 2005). The present study showed that subjective health and functional status explained all or most of the depression-chronic disease link for all chronic illnesses.…”
Section: Discussionsupporting
confidence: 94%
“…This may be explained by the fact that elderly subjects are so preoccupied with either positive or negative personal events that they report fewer complaints. Similar to previous studies [20,21] , advanced age and presence of musculoskeletal disorders contributed to depression scores.…”
Section: Discussionsupporting
confidence: 88%
“…It has recently been shown that the presence of multiple chronic medical conditions increases the likelihood of depressive symptoms [11]. Suicide appears to be more strongly associated with depression in the elderly than in younger age groups [12].…”
Section: Introductionmentioning
confidence: 99%